Pelatihan Penerapan Pendekatan STEAM dalam Pengembangan Bahasa dan Literasi Anak Usia Dini bagi Guru TK di Kabupaten Takalar - Amal, Azizah (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of language and literacy skills is an essential aspect of early childhood education, as it serves as the foundation for children’s readiness to enter formal education. However, learning practices in several kindergartens are still dominated by conventional methods that provide limited exploratory and contextual learning experiences. This community service activity aims to enhance kindergarten teachers’ competencies in implementing the STEAM approach in the development of early childhood language and literacy skills. The program was conducted through training and mentoring sessions for kindergarten teachers in Takalar Regency District. The methods employed included socialization activities, training on STEAM concepts, workshops on designing STEAM-based learning activities, and assistance in classroom implementation. Data were analyzed descriptively based on observation results, participant response questionnaires, and activity documentation. The results of the program indicated an improvement in teachers’ understanding of the STEAM concept and their ability to design more creative and interactive language and literacy learning activities. Teachers were also able to integrate elements of science, technology, engineering, arts, and mathematics into play-based learning activities. Therefore, this training made a positive contribution to improving teachers’ pedagogical competencies and encouraging innovation in literacy learning for early childhood education.